Characteristics of Chicken Meatballs with the Addition of White Oyster Mushroom (Pleurotus ostreatus) - Anwar, C.; Irhami; I. R. Aprita; Irmayanti; M. Kemalawaty (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2025)
Processed products in the form of gels made from meat protein, can be beef, chicken, or fish are meatballs which are made from ground beef with additives such as salt, tapioca flour and spices. This study was intended to investigate the dosage of white oyster mushroom supplementation on the quality characteristics of chicken meatballs. This study adopted a complete randomized design (CRD) with a dose of oyster mushroom supplementation which included 4 (four) treatments, namely A = 0%, B = 15%, C = 25% and D = 35% with 5 repetitions and 20 experimental units were obtained. The research variables included yield, ash content, and sensory analysis (color, taste, aroma, and texture). The results indicated that different levels of white oyster mushroom addition (0%, 15%, 25%, 35%) did not have a significant (P>0.05) effect on the color, taste, and texture of the meatballs but had a significant impact (P<0.05) on the yield and ash content as well as the sensory aroma of chicken meatballs. The highest-quality chicken meatballs were obtained with a 35% white oyster mushroom supplement, with product characteristics of ash content 1.69%, yield 94.6%, aroma 3.58, color 3.54, taste 3.20, and texture 3.70.